On the identity of Mastacanthus Suffrian, 1852 and Sternoglosus Suffrian, 1866 and key to World genera of Pachybrachina (Chrysomelidae: Cryptocephalinae: Cryptocephalini) - M. L. Chamorro (Кавказский энтомологический бюллетень, 2013)
Pachybrachina includes 8 genera worldwide. The identity of the two Neotropical genera Mastacanthus Suffrian, 1852 and Sternoglosus Suffrian, 1866 is established. Redescription of the type species of both genera and an illustrated key to World genera are provided. The generic type species of Sternoglosus and the lectotype for S. scalaris are designated